Concept of Religious Tolerance among Ulama of Traditional Pesantren in Sukabumi, West Java - Abdillah Abdillah; Wan Zailan Kamaruddin bin Wan Ali (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
Pesantren nowadays has been accused by the West as a nest of radicalism and terrorism. Not without reason, in Indonesia, many intolerance and violence issues have involved several Muslim communities and alumni of pesantren. Therefore, in this study, the authors intimately will explore the views of traditional pesantren ulama, mainly in Sukabumi, on some issues of religious tolerance. In this study, the authors used a qualitative approach by using a semi-structured interview and analysis document as a data collection. After that, the data will be analyzed qualitatively. This study found that traditional pesantren ulama in Sukabumi understood the concept and discourse of religious tolerance. They have moderate views and attitudes towards non-Muslims. However, some traditional pesantren ulama in Sukabumi refused to tolerate several cases like sending greetings and attendance at Christmas celebration. These ulama also have a different opinion towards Ahmadiyyah minority group. One Kyai has a gruff view and attitude towards Ahmadiyyah groups. Meanwhile, two other ulama refused to commit violence against Ahmadiyyah and other groups.